Sharing economy: Crafting temporal identity and legitimacy claims as an emergent category - Cotrim, J. (Abstract book: 14th Annual International Conference on SMEs, Entrepreneurship and Innovation, 2017)
Typically involving the use of information technologies to link different stakeholders with the goal of using surplus resources in the creation of valuable products and services, the sharing economy (SE) is growing at an impressive rate across the globe (Cohen & Kietzmann, 2014). However, in general there is a lack of common understanding of SE and its underlying mechanisms (Knote & Blohm, 2016). Despite this ambiguity, SE represents a clear change in how businesses are organized, and many established companies are looking at SE businesses as sources of inspiration to undertake improvements in their own business models. In this context, SE is raising a number of questions related to conventional management theories. As an emergent category, SE should be an important resource for the establishment of organizational identity and legitimacy, especially in new business. As innovative organizations, SE entities are coming up with divergent business models whose characteristics are only partially described. In this research, we address these by studying how has the category of SE evolved, that is the processes by which external audiences are giving identity legitimacy to SE as a category. To answer this research question, were conducted two studies: 1) a literature review on how new categories emerge and legitimacy is construed; and 2) an historical analysis of the expression SE or its equivalents, which implicated the collection of secondary data. More precisely, content analysis was conducted to identify the mechanisms used by different actors to establish SE as a legitimate category. This paper presents a more robust framework and detailed understanding of the sharing economy field in its nascent dimension.